Multi-simulation environment for smart grid : co-simulation approach - Palizban, Omid; Kauhaniemi, Kimmo (IEEE, 2020)
Wide area measurement and control methods should be employed in modern grids to ensure a more resilient power system. Digital communication technologies play a vital role in such systems, and delays in the communication system can lead to malfunctions in the power system. The integration of the power system and communication network is thus a requirement for implementing smart grids. This paper investigates the possibility of comprehensive integration and discusses the challenges to coupling power system with communication network using continuous and discrete simulation techniques, respectively. The frameworks, platforms, and possible interfaces for a high-performance cosimulation are also presented; the effects of time synchronization and method for obtaining the accrued result are investigated. Finally, existing co-simulation methods are summarized in a table.
Keywords: communication system; co-simulation; smart grid; time synchronization; power system; fi=Sähkötekniikka|en=Electrical Engineering|